2006
DOI: 10.2355/isijinternational.46.106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polyethylene Glycol on the Morphology of Zn Electrodeposited on Steel Sheet

Abstract: Zn electrodeposition was carried out on a steel sheet galvanostatically at 1 500 A/m 2 in un-agitated sulfate solution of 40°C to investigate the effect of Polyethylene Glycol (PEG) addition on the morphology of Zn. In situ observation by atomic force microscopy showed that the growth of deposited Zn proceeded through the advance of macro-steps in platelet crystals to the [2130] direction. The addition of PEG to the solution brought about a decrease in size and macro-step height and an increase in inclination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 17 publications
0
10
1
Order By: Relevance
“…Consequently, the intensity of diffuse reflection is strong in the case of Zn deposited with preferred {0001} plane orientation, resulting in an increase in the lightness of Zn. 24) However, in this study, the lightness increased with preadsorption despite the decrease in {0001} plane orientation. This suggests that the size of Zn platelet crystals has a greater effect on the lightness than crystal orientation.…”
Section: Crystal Orientation Of Deposited Zncontrasting
confidence: 60%
“…Consequently, the intensity of diffuse reflection is strong in the case of Zn deposited with preferred {0001} plane orientation, resulting in an increase in the lightness of Zn. 24) However, in this study, the lightness increased with preadsorption despite the decrease in {0001} plane orientation. This suggests that the size of Zn platelet crystals has a greater effect on the lightness than crystal orientation.…”
Section: Crystal Orientation Of Deposited Zncontrasting
confidence: 60%
“…It is reported that the grains of the deposits consist of many particles with a size of several tens of nm. [16][17][18][19][20] In this study, the particle size determined using a half width of X-ray diffraction pattern appears to correspond to the size of each particle forming the deposited Ni grains. As shown in Fig.…”
Section: Resultsmentioning
confidence: 69%
“…15,16) The suppression of Zn normal lateral growth appears to have an effect on the morphology of deposited Zn. The decrease in the size and the increase in inclination of Zn platelet crystals by the preadsorption, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%